La virgen de los sicarios: a critical reading of the Colombian violence ending the twentieth century - Caballero, Juliany Andrea; Ortega, Liseth Marcela; Suárez, Johana Paola (Rastros Rostros, 2011)
This article is based on research into “Political proposals reflected in the Colombian novels of the twentieth century” of Universidad Cooperativa de Colombia, Bucaramanga, 2009, specifically in La virgen de los sicarios written by the Colombian author Fernando Vallejo Rendón. Fernando Vallejo writes this novel at the end of the XX century, showing the violent situation that Medellin confronted in the 90s, due to the war among and against the Pablo Escobar ́s drug traffic criminal groups and a juvenile population murderess and hungry of money. To justify the history in which the novel is developed, we have the spaces of the author’s experience. Equally with a critical literary analysis of the novel and a pedagogic proposal to carry out the novel at the school.